Grassroots Community Movement Towards New Province Formation and City Development in Jambi Province, Indonesia - Karim, Navarim; Rohayati, Wahyu; Maisyarah, Nyimas Dian (Journal of Governance and Public Policy, 2026)
This research aims to analyze the movement, discursively constructed by grassroots communities, regarding the need for new regional development that is more socially, economically, and politically accommodating, currently administratively located in Jambi Province. This research employs a mixed-methods approach to gather and analyze the data. The results show that grassroots communities have a dominant discourse on the creation of new provinces and on city development. It is based on considerations of public service and governance effectiveness, strengthening regional autonomy, and advancing local democracy through community empowerment. Secondly, social media plays a vital role in vocalizing the discourse on the formation of a new province and development. Third, despite a discourse on city development and the creation of new provinces, this study found that there are decentralization dilemmas and socio-cultural challenges associated with the separation and unification of several districts with different cultural roots. This study concludes that although this movement is within a deconcentration dialectic, revealing persistent structural and cultural challenges, it strongly affirms the consciousness and efforts to radicalize an autonomy and democratic strengthening that is centralized at the grassroots level. Therefore, within the dialectic of decentralization, this highlights the importance of policymakers maintaining inclusive dialogue and incorporating public will, as the group most impacted by development policies.